"At First I Couldn't Catch My Breath": Process and Strategies for Managing Chronic Obstructive Pulmonary Disease. (March 2018) - Genoe, M. Rebecca; Zimmer, Chantelle
In this article, we describe the process and strategies that study participants living with chronic obstructive pulmonary disease in central Canada utilized to manage and live well with their illness and its associated symptoms. Drawing on interpretive phenomenology, we interviewed eight participants three times, followed by a member checking focus group and individual interviews. We analyzed interview transcripts using detailed line by line analysis. Our findings suggest participants engaged in a challenging process of recognizing that changes had occurred and then coming to terms with these changes by acknowledging the severity of their condition and the resulting limitations. Then, participants drew upon several strategies to minimize feelings of breathlessness, including taking care of themselves, managing risk, and altering behavior. Participants acknowledged the challenges inherent to this process, yet described how they were able to live well with chronic obstructive pulmonary disease through their adaptations.